Determinant of Employee Engagement and Productivity: An Analysis of Work Motivation, Competence - Agustian Zen (International Journal of Business and Applied Economics, 2023)
It shows that the variables in the field of human resources offered in this scientific article reinforce through the existing literature review, by looking at and being stretched as in result of the author's perspective. An ascientific article is that it can  be continued in  this variable  can be used by  other researchers together  into one variable in a research   result.